Why aid is unpredictable: An empirical analysis of the gap between actual and planned aid flows - Gustavo Javier Canavire-Bacarreza; Eric Neumayer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2014)
Aid flows continue to be volatile and unpredictable, even though it is widely accepted that this erodes the effectiveness of foreign aid. We argue that fragmented donor-recipient relationships, notably the large number of minor aid relations that tend to be associated with donors' desire to have 'fly their flag' around the world, increase aid unpredictability. Our empirical analysis of the determinants of aid unpredictability suggests that aid becomes less predictable with more fragmented donor-recipient relationships. Specifically, the effect of fragmentation on overshooting previous spending plans is statistically highly significant and substantively important. In contrast, fragmented donor-recipient relationships have no effect on the shortfall of actual aid compared to donors' spending plans.
Keywords: F35; 330; aid predictability; donor fragmentation; forward spending plans